2021
DOI: 10.3390/medicina57010055
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship between COVID-19 and Hyponatremia?

Abstract: Nowadays, humanity faces one of the most serious health crises, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. The severity of coronavirus disease 2019 (COVID-19) pandemic is related to the high rate of interhuman transmission of the virus, variability of clinical presentation, and the absence of specific therapeutic methods. COVID-19 can manifest with non-specific symptoms and signs, especially among the elderly. In some cases, the clinical manifestations of hyponatremia may be the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 28 publications
1
53
0
Order By: Relevance
“…Interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF) play a pivotal role in the development of sepsis. IL-6 has an inverse correlation with serum sodium which has a mechanism to stimulate hypothalamic arginine vasopressin (9)(10)(11)(12). Several studies showed that pneumonia is associated with syndrome of inappropriate antidiuretic hormone (11,13,14); this mechanism may cause hyponatremia.…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF) play a pivotal role in the development of sepsis. IL-6 has an inverse correlation with serum sodium which has a mechanism to stimulate hypothalamic arginine vasopressin (9)(10)(11)(12). Several studies showed that pneumonia is associated with syndrome of inappropriate antidiuretic hormone (11,13,14); this mechanism may cause hyponatremia.…”
Section: Introductionmentioning
confidence: 99%
“…It can result from low oral intake of fluids, diarrhea, diuretics, and in many instances, it has been attributed to the syndrome of inappropriate antidiuretic hormone secretion (SIADH). Symptoms of hyponatremia such as nausea, dizziness, and headache have been reported in COVID-19 [4]. However, seizure in the context of COVID-19associated hyponatremia, to the best of our knowledge, was not previously reported.…”
Section: Introductionmentioning
confidence: 74%
“…SIADH is diagnosed by a combination of supportive laboratory tests (including serum and urine sodium level, serum and urine osmolality) and the exclusion of other causes of hyponatremia [6]. COVID-19 related hyponatremia was reported frequently in COVID-19 patients, and it could be the only presenting manifestation [4,7]. The mechanism of COVID-19-induced SIADH is not well elucidated, but it was postulated that inflammatory cytokine release [4], stress, intravascular volume depletion, lower osmolarity, and ventilation perfusion-mismatch play a role in dysregulating the antidiuretic hormone (ADH) release [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, it is addressed a so-called droplet infection, which is transmitted through the air. Coronavirus is spread through the air not only by droplets but also by aerosols [22]. Spreading of the aerosols is more dangerous because they are smaller particles than droplets [21,23].…”
Section: Properties Of Coronavirus and Its Dissemination And Transmissionmentioning
confidence: 99%